(untitled) (Research, Society and Development, 2022)
This study aimed to evaluate the efficiency of thermotherapy in the control of pathogens in corn seeds and their germination power. The same was developed in the Phytopathology laboratory of the Universidade Federal Rural da Amazônia, Campus Belém, PA. For this, the experimental design used was completely randomized (DIC), with 6 treatments and five replications, each repetition consisted of a batch of 20 seeds. The heat treatments used were by immersion in heated water at the following temperatures: 40 oC, 50 oC, 60 oC, 70 oC and 80 oC, being called, T2, T3, T4, T5, T6 and T7, respectively. After the seeds were submitted to the treatments, the sanity was analyzed to determine the efficiency of the treatments in the fungal reduction of the seeds and germination. Thermotherapy was efficient in relation to the control in all treatments in the fungal reduction of the seeds, highlighting the treatments T5 and T6. In germination, this method obtained positive results in treatments T2 and T3, obtaining 60% and 98% of germination in relation to the control. Thus, thermotherapy proved to be a positive alternative method in reducing the fungal potential of corn seeds and increasing germination power at certain temperatures.